Socio-cultural and Economic Impacts of Religious Festivals on Sustainable Local Community Livelihoods in Kerala: The Case of Palakkad - Nair, Bindu V. T. (The international journal of religious tourism and pilgrimage, 2022)
Festivals depict the heritage, culture, and traditions of a particular region. They create a state of exhilaration and enthusiasm. Kerala is a state in southwest India with its own distinct culture and traditions. The state is also known for its religious pluralism. This study attempts to understand the perceived impact of religious festivals on the local community livelihoods in Palakkad, a district in central Kerala. Twelve temples in which religious festivals are held annually, with attendance in the range of thousands, were selected. The selected temples are famous for hosting specific religious festivals which attract a large number of visitors, from within and beyond the region. Using a sample of 420 community members living around these temples, this study examined how the socio-cultural and economic impacts of these religious festivals are perceived by the community. The findings show that there is a statistically significant relationship between the perceived socio-cultural and economic impacts of festivals on local communities. The celebration of local values and distinctiveness were evident in these religious festivals. The local community considers these festivals as part of their community identity and as offering impetus for annual family and community reunions.